Innate T-αβ lymphocytes as new immunological components of anti-tumoral “off-target” effects of the tyrosine kinase inhibitor dasatinib - Barbarin, Alice (Sci Rep, 2020)
Kinase inhibitors hold great potential as targeted therapy against malignant cells. Among them, the tyrosine kinase inhibitor dasatinib is known for a number of clinically relevant off-target actions, attributed in part to effects on components of the immune system, especially conventional T-cells and natural killer (NK)-cells. Here, we have hypothesized that dasatinib also influences non-conventional T-αβ cell subsets known for their potential anti-tumoral properties, namely iNKT cells and the distinct new innate CD8 T-cell subset. In mice, where the two subsets were originally characterized, an activated state of iNKT cells associated with a shift toward an iNKT cell Th1-phenotype was observed after dasatinib treatment in vivo. Despite decreased frequency of the total memory CD8 T-cell compartment, the proportion of innate-memory CD8 T-cells and their IFNγ expression in response to an innate-like stimulation increased in response to dasatinib. Lastly, in patients administered with dasatinib for the treatment of BCR-ABL-positive leukemias, we provided the proof of concept that the kinase inhibitor also influences the two innate T-cell subsets in humans, as attested by their increased frequency in the peripheral blood. These data highlight the potential immunostimulatory capacity of dasatinib on innate T-αβ cells, thereby opening new opportunities for chemoimmunotherapy.